Praktik Money Politic dalam Pemilu di Indonesia Perspektif Fiqih Siyasah dan Hukum Positif - Nanda Puji Istiqomah; M. Noor Harisudin (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2021)
Indonesia as a country that adheres to a democratic system, general elections are a way to determine a leader. However, in practice there is still a lot of buying and selling votes or money politics (money politics) which is also referred to in Islam as rasywah (bribes). Where this is a form of violation of democracy and the perpetrators can be punished. The presence of Law no. 7 of 2017 Elections, regulations on the General Election Commission (KPU) and the Election Oversight Body (Bawaslu) regulations are expected to be able to reduce violations that occur during elections. This phenomenon is also responded to by both positive law and siyasa fiqh. The author uses library research methods, namely research that uses library materials as the main source (data), in the form of laws and regulations, books, the Qur'an, Hadith and all literature related to research.